Effectiveness of Computer-Based Sexual Communication Program for Mothers and Pre-Adolescent Daughters: A Quasi-Experimental Study - Promneramit, Pawana; Phuphaibul, Rutja; Phumonsakul, Srisamorn; Sinsuksai, Nittaya (Pacific Rim International Journal of Nursing Research, 2021)
Adolescent sexual risk behaviors are a problem that may have long-term health outcomes. Many strategies and interventions are needed around the world to reduce these risks. This quasi-experimental study examined the effects of the computer-based Mother-daughter Sexual Communication-Thailand Program developed to increase positive attitudes, subjective norms, perceived behavioral control, and intention focused on mothers’ sexual communication behaviors and daughters’ sexual abstinence intention in an attempt to reduce adolescent risk behavior. The participants were mothers and their pre-adolescent daughters in elementary schools in Bangkok, Thailand. The intervention group (n=37) received one session weekly for five consecutive weeks of the program, whereas the control group (n=40) did not receive the intervention. Eight instruments were used to collect data from the mothers and pre-adolescent daughters before the intervention and at Week 5 immediately after the intervention and at one month after the completion of the intervention. Data were analyzed by Generalized Estimating Equations The results indicated that the mothers in the intervention group had statistically significant higher positive attitudes, perceived behavioral control, and intention at one month after the intervention in addition to better sexual communication behaviors immediately after the intervention than those in the control group. However, the mothers’ subjective norms and the daughters’ sexual abstinence intentions were not significantly different between the two groups. This program will be undergoing further testing and possible modification for adolescents’ health promotion.